2013
DOI: 10.1007/s10517-013-2146-9
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of ARE-Inducing Phenol Antioxidant TS-13 in Chronic Inflammation

Abstract: The protective effect of partially substituted monophenol TS-13 inducing the Nrf2/Keap1/ARE signaling system was studied on the model of chronic inflammation in vivo. It was found that during simulation of inflammation in an air pouch lined with synovial-like membrane, TS-13 did not affect the exudate volume, protein content, and cell count, but significantly reduced the intensity of oxidative metabolism in leukocytes of the exudate. In rheumatoid polyarthritis induced by heterologous collagen, TS-13 reduced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In the absence of external stimulation, Nrf2 is in the cytoplasm and binds to inactivated KEAP1. When ROS accumulates, there are conformational changes in KEAP1, making it disassociate from Nrf2 and translocate into the nucleus [69]. Musculoaponeurotic fibrosarcoma (Maf ) protein forms a heterodimer with Nrf2 and then combines with ARE to enhance the expression of downstream phase II antioxidant genes, producing antioxidant enzymes [70].…”
Section: Nrf2 Signaling Pathwaymentioning
confidence: 99%
“…In the absence of external stimulation, Nrf2 is in the cytoplasm and binds to inactivated KEAP1. When ROS accumulates, there are conformational changes in KEAP1, making it disassociate from Nrf2 and translocate into the nucleus [69]. Musculoaponeurotic fibrosarcoma (Maf ) protein forms a heterodimer with Nrf2 and then combines with ARE to enhance the expression of downstream phase II antioxidant genes, producing antioxidant enzymes [70].…”
Section: Nrf2 Signaling Pathwaymentioning
confidence: 99%
“…The efficacy of antioxidant therapy in the air pouch model has been investigated by others. Drugs including 10-(6′-plastoquinonyl)­decyltriphenylphosphonium bromide (SkQ1), Cressa cretica extract, TS-13 (a tert -butyl phenol thiosulfonate), and atorvastatin have shown anti-inflammatory effects in this model. These results are promising; however, all of these treatment options required prophylactic administration 1 h or 1–10 days (daily) before carrageenan injection to achieve therapeutic efficacy. In contrast, coadministration of our optimized TEMPO copolymer reduced both O 2 •– and TNFα levels in the air pouch by ∼90% and ∼83%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This effect is achieved through its interaction with erythroid-derived nuclear factor 2 (Nrf2), a transcription factor that modulates the expression of genes containing antioxidant response elements (AREs). The activation of the Nrf2/ARE pathway promotes the expression of antioxidant genes and stimulates the production of SOD, GPx and Cat enzymes, whose function is to eliminate ROS [ 58 , 59 ]. In this sense, it has been observed that RV activates Nrf2 through the activation of AMPK, which, in turn, stimulates the Nrf2/ARE pathway and, as a result, increases the production of antioxidant enzymes [ 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the Nrf2/ARE pathway promotes the expression of antioxidant genes and stimulates the production of SOD, GPx and Cat enzymes, whose function is to eliminate ROS [ 58 , 59 ]. In this sense, it has been observed that RV activates Nrf2 through the activation of AMPK, which, in turn, stimulates the Nrf2/ARE pathway and, as a result, increases the production of antioxidant enzymes [ 58 , 59 , 60 ]. In our study, we found a non-significant increase in SOD activity in EG1000 and a statistically significant decrease in the PG, which agrees with what was stated above, as well as with the results of two randomized double-blind clinical trials in which an increase in SOD activity was observed with RV treatments in doses of 500 and 800 mg/day, and a decrease in the activity of the enzyme was observed in groups treated with a placebo [ 55 , 61 ].…”
Section: Discussionmentioning
confidence: 99%